The triumph of neoliberalism and the world dominance of capitalism. (1st June 2015) - Senker, Peter
Abstract : Neoclassical economics dominates modern economics and provides an important theoretical basis for neoliberalism. Among its inadequacies are failure to take sufficient account either of technological change or of marketing activities, both of which are central features of modern capitalism. Neoliberals believe that the state should be confined to safeguarding individual and commercial liberty and strong property rights. But in practice, corporations' dependence on states has been pervasive for at least 100 years. Corporations aim to secure higher profits. They lobby international organizations, as well as states, both to create conditions more favourable to their own individual interests, and also to increase the proportion of economies in which private corporations are allowed to operate. This may apply, for example, to privatization of health and education services which is not always in the public interest. This paper outlines several examples of interactions among corporations, technological change, marketing, state support and international organizations. Examples include huge state support for road construction, which facilitated the domination of cars over land transport; the role of marketing and technological change in the food and agricultural industries; and state support for scientific and technological change in semiconductors and the Internet, and for the development of biotechnology. In conclusion, the paper suggests an alternative approach to studying the dynamics of the modern world economy, viewing it as complex networks of interlocking systems. This might produce more useful analyses than those based on obsolete theories.